Use of Oxyrase® enzyme to enhance recovery of Escherichia coli O157:H7 from culture media and ground beef - H. Thippareddi; K. Kone; Randall K. Phebus; Daniel Y.C. Fung; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 1994)
Escherichia coli O157:H7 is a bacterium that has caused great concern in the meat and food industry during the last few years because of several, well-publicized, disease outbreaks, including the incident at the Jackin- the-Box fast food chain in Seattle, Washington. The organism can cause severe sickness and even death in certain population groups. To better assure meat safety, federal meat inspection is focusing on developing rapid methods to detect this disease agent and others. Oxyrase is a commercially available enzyme that can accelerate the growth of some bacteria. Current techniques for isolation and culturing of E. coli O157:H7 from foods require an enrichment period of 18 to 24 hours, thus limiting their usefulness for perishable foods that are marketed quickly. Our investigation found that Oxyrase shortened required enrichment periods in broth culture only. The enzyme was less effective in sterilized ground beef.
Keywords: Cattlemen' s Day; 1994; Kansas Agricultural Experiment Station contribution; no. 94-373-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 704; Beef; Escherichia coli O157:H7; Oxyrase; Ground beef; Rapid methodology; Meat safety